Investment Project Analysis Of Extra Facility Business Model Case Study: Pt. Pln (Persero) Riau And Riau Islands Distribution Units - Silvia Iriani; S. K. Wiryono (Journal Of Social Science (JoSS), 2023)
The development of disruptive business and technology has the potential to reduce the growth of electricity sales. The existence of "Indirect competitors" who also take advantage of the use of assets that do business in the electric vehicle ecosystem, companies providing solar PV rooftop services, and the emergence of new business areas will be a challenge for PLN. Companies must develop a business model strategy to ensure the company's financial sustainability, which ultimately ensures the sustainability of the electricity business in the future. Real improvements are expected to help companies increase revenue, efficiency, and cost effectiveness which can ultimately contribute to company revenue. Through the Extra Facilities business model, as a form of service to meet changing market tastes, sales strategies need to be implemented for customers who have special standards and needs. In this regard, the author carried out an analysis of the investment for connecting Extra Facility services to one of the prospective PLN customers of the Riau and Riau Islands Distribution Main Unit using a build-operate-transfer (BOT) scheme. The feasible indicator that was being used was financial profitability, resulting in IDR. 6,914,249,547 NPV higher than zero. Moreover, this project also gives certain commitment by generating 17.56% IRR > WACC with a payback period of 4 years 8 months less than 10 years (based on the term of the agreement).